Fungal Isolation and the Production of its Biomass in a Palm Oil Medium - Che Omar, Ibrahim; Suan Li, Lee (Universiti Putra Malaysia Press, 1993)
A fungus which was identified to be Rhizopus arrhizus was selected as a potential microorganism for the production of biomass using a palm oil medium. Using the optimized medium composition and culture conditions (%, w/v) : palm oil, 4.0; peptone, 2.0; Mg S04' 7H20, 0.07; NaC!, 0.5; CaCI2.2H20, 0.01; Tween 20, 1.2, pH 7.0 at 37"C, agitation speed, 200 rpm and inoculum size, 1 X 104 spores/ml, a maximum biomass production and fat consumption of about 16.2 gil and 82%, respectively, were obtained. Compared to the unoptimized conditions, this is an increase of 62% and 105% in biomass production and fat consumption, respectively. Proximate analysis of the biomass revealed.that the protein and nucleic acid content were 42.8 and 2.2%, respectively. Amino acid profiles were found to be comparable to those of the FAO reference.